Prepectoral Revision Breast Reconstruction for Treatment of Implant-Associated Animation Deformity: A Review of 102 Reconstructions. (20th January 2018) - Gabriel, Allen; Sigalove, Steven; Sigalove, Noemi M; Storm-Dickerson, Toni L; Rice, Jami; Pope, Nicole; Maxwell, G Patrick
Abstract: Background: Animation deformity is a direct consequence of subpectoral implant placement for breast reconstruction following mastectomy. Current treatment options ameliorate but do not address the source of the problem. Moving the implant from subpectoral to prepectoral has the potential to eliminate animation deformity. Objectives: Describe the technique and outcomes of prepectoral revision reconstruction in over 100 cases and discuss patient selection criteria for a successful outcome. Methods: Patients who presented with animation deformity following two-stage implant reconstruction were included in this retrospective study. Revision surgery involved removal of the existing implant via the previous incision site along the inframammary fold, suturing of the pectoralis major muscle back to the chest wall, creation of a prepectoral pocket for the new implant, use of acellular dermal matrix to reinforce the prepectoral pocket and completely cover the implant, and fat grafting to enhance soft tissue. Patients were evaluated for resolution of animation deformity and occurrence of complications during follow up. Results: Fifty-seven patients (102 breasts) underwent prepectoral revision reconstruction with complete resolution of animation deformity. Complications occurred in 4 breasts (3.9%) and included seroma (2 breasts), skin necrosis (3 breasts), and wound dehiscence (1 breast). All 4 breasts with complications had their implants removed and replaced. There were no incidences of infection or clinically significant capsular contracture in this series. Conclusions: Revision reconstruction with prepectoral implant placement and complete coverage with acellular dermal matrix resolves animation deformity and results in aesthetically pleasing soft breasts. Patient selection is critical for the success of this technique. Level of Evidence: 4: